From Social Distancing to Physical Distancing: A Challenge for Evaluating Public Health Intervention against COVID-19 - Pratomo, Hadi (UI Scholars Hub, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has affected every country. Currently, no suitable vaccine or treatment has been identified; therefore, each country has attempted to issue appropriate policies, designed to reduce and prevent increases in the numbers of extreme cases. Transmission can be prevented by implementing social restrictions, also known as social distancing. The World Health Organization (WHO) has issued several methods for the prevention of transmission, including social distancing, washing hands with soap (or using hand sanitizer containing at least 70% alcohol), and using masks. Over time, the term social distance has changed to physical distance. Evaluating the impacts of different types of non-pharmacological interventions has been challenging.